Energy-Efficient Smart Temperature Sensors in CMOS Technology - Souri, Kamran (Analog Circuits and Signal Processing,, 2018)
This book describes the design and implementation of energy-efficient smart (digital output) temperature sensors in CMOS technology. To accomplish this, a new readout topology, namely the zoom-ADC, is presented. It combines a coarse SAR-ADC with a fine Sigma-Delta (SD) ADC. The digital result obtained from the coarse ADC is used to set the reference levels of the SD-ADC, thereby zooming its full-scale range into a small region around the input signal. This technique considerably reduces the SD-ADC's full-scale range, and notably relaxes the number of clock cycles needed for a given resolution, as well as the DC-gain and swing of the loop-filter. Both conversion time and power-efficiency can be improved, which results in a substantial improvement in energy-efficiency. Two BJT-based sensor prototypes based on 1st-order and 2nd-order zoom-ADCs are presented. They both achieve inaccuracies of less than ±0.2°C over the military temperature range (-55°C to 125°C). A prototype capable of sensing temperatures up to 200°C is also presented. As an alternative to BJTs, sensors based on dynamic threshold MOSTs (DTMOSTs) are also presented. It is shown that DTMOSTs are capable of achieving low inaccuracy (±0.4°C over the military temperature range) as well as sub-1V operation, making them well suited for use in modern CMOS processes. Presents a new readout technique (the zoom-ADC) to address the implementation of energy-efficient temperature sensors in CMOS technology; Shows how this technique can be used to design energy-efficient temperature sensors without compromising other key specifications, such as accuracy and resolution; Shows how this technique can be used to design general-purpose incremental ADCs that can achieve both high resolution and state-of-the-art energy efficiency; Presents DTMOST-based temperature sensors, which achieve significantly higher accuracy than previous all-CMOS temperature sensors.